Cannabis use and the course and outcome of major depressive disorder: A population based longitudinal study. (May 2017) - Feingold, Daniel; Rehm, Jürgen; Lev-Ran, Shaul
Abstract: Cannabis use has been reported to affect the course of various psychiatric disorders, however its effect on the course of major depressive disorder (MDD) is not yet clear. We used data from Wave 1 and Wave 2 of the National Epidemiologic survey on Alcohol and Related Conditions (NESARC). Individuals with baseline MDD (N=2, 348) were included in the study. Cannabis users without a Cannabis Use Disorder (CUDs) and individuals with a CUD were compared to nonusers using linear and logistic regression analyses controlling for sociodemographics, psychiatric disorders and substance use disorders at baseline. No differences were found in rates of remission between the groups. Level of cannabis use was associated with significantly more depressive symptoms at follow-up, particularly anhedonia, changes in body weight, insomnia or hypersomnia and psychomotor problems. After adjusting for baseline confounding factors, no associations were found between cannabis use and suicidality, functionality and quality of life. We conclude that many of the associations between cannabis use and a more severe course of MDD do not seem to be attributed to cannabis use itself but to associated sociodemographic and clinical factors. Further longitudinal studies using depression severity indices are required. Highlights: Individuals with baseline major depressive disorder were followed over a three-year time period. Cannabis users and individuals with cannabis use disorders were compared to nonusers. No differences were found in rates of remission between the groups. Level of cannabis use was associated with significantly more depressive symptoms at follow-up. These findings did not retain significance after adjusting for baseline confounding factors.